Computer Axial Tomography and evoked potentials as predictors of clinical improvement in cranioencephalic trauma. - José Ramón Tejera del Valle; Florencio Pons Moscoso; Joaquín Aguilar Trujillo; Yarima López Puig; José Arteaga Bermúdez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Mortality predictors in cranioencephalic trauma reveal mortality chances or possible severe sequels; but they do not predict rehabilitation possibilities. Objective: To assess the effectiveness of Computer Axial Tomography and evoked potentials to predict clinical improvement six moths after cranioencephalic trauma. Method: Prospective, observational, descriptive study developed from January to December, 2006, to assess the effectiveness of Computer Axial Tomography and evoked potentials as possible predictors of clinical improvement in an adult population (64 patients) of Cienfuegos province suffering from cranioencephalic trauma. Results: Patients with less serious lesions had three times more chances of clinical improvement. Patients with normal evoked potentials had greater chances of clinical improvement compared with those presenting irregular evoked potentials. Conclusions: The study showed the predictive value of computer axial tomography and evoked potentials related with clinical improvement in patients with cranioencephalic trauma.